A metaphorical application of the concept ‘paradigm’ to the public relations domain - Benita Steyn (Communicare)
The aim of this conceptual analysis of Kuhn’s paradigm theory was to explore whether the concept of paradigm could be applied to the public relations domain—specifically with regard to concepts such as dominant paradigm, paradigm debate, paradigm struggle and scientific revolution. Based on the findings, the author suggests that the first three models of public relations are the theory that represents the origins of public relations as a (social) science; that the dominant paradigm of normal science practice in public relations is persuasion; and that alternative paradigms debated are about inter alia professionalism, ethical performance, conflict, chaos and pluralism. Furthermore, an important paradigm debate is currently taking place between eminent US scholars (relationships) and European scholars (reflection). However, the real paradigm struggle is seen to be between persuasion and two-way symmetrical communication (regarded by some as a struggle between symbolic and behavioural relationships). The author’s conclusion is that public relations is currently suffering an identity crisis which could, with a number of alternative paradigms available, lead to a scientific revolution in the discipline.